Exploring Mixed Reality in Digital Board Games: A Comparative Analysis of Cooperative and Competitive Modes - Moreira, Victor Emanuel Montes; Almeida, Lucas Gregory Gomes; Catapan, Márcio Fontana; Munhoz, Daniella Rosito Michelena; Maia, André Leonardo Demaison Medeiros; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
The integration of mixed reality (MR) into digital board games introduces new dimensions of player engagement and satisfaction. This study examines the impact of MR on user experience by comparing cooperative and competitive game modes. Using the games "Demeo" (cooperative) and "Demeo Battles" (competitive) as case studies, we conducted playtesting sessions and applied the GUESS-18 scale to measure various aspects of player satisfaction, including usability, narrative engagement, pleasure, and social connectivity. Our findings revealed significant differences in user experience between the two game modes. Cooperative play in "Demeo" was associated with higher levels of social connectivity, pleasure, and in-game engagement, indicating a preference for collaborative interactions and immersive experiences. By contrast, "Demeo Battles" excelled in personal gratification and visual aesthetics, highlighting the competitive mode's focus on individual performance and strategic depth. Additionally, we evaluated the impact of different VR headsets (Quest 2, Quest 3, and Quest Pro) on the mixed reality experience. Quest Pro provided the highest overall satisfaction due to its more ergonomic and comfortable design, which enhanced comfort and facilitated more immersive mixed reality experiences. These insights offer valuable guidance for future game design, emphasizing the importance of tailoring MR experiences to player preferences, in both cooperative and competitive contexts.